2009
DOI: 10.1158/0008-5472.can-08-1693
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Polo-like Kinase 1 as a Potential Therapeutic Target in Anaplastic Thyroid Carcinoma

Abstract: Anaplastic thyroid carcinoma (ATC) is one of the most aggressive and chemoresistant cancers. The serine/threonine kinase Polo-like kinase 1 (PLK1), a key regulator of multiple steps during mitotic progression, is highly expressed in ATC. Here, we used the BI 2536 PLK1 inhibitor on ATC and nontransformed thyroid follicular cell lines. Our data show that ATC cells are addicted to high levels of PLK1 activity for proliferation, survival, anchorage-independent growth, and tumorigenicity. On treatment with nanomola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 38 publications
7
47
0
Order By: Relevance
“…4B). This efficacy was previously observed in other murine models (41,47,(56)(57)(58)(59), and provided the rationale for the clinical trials.…”
Section: Chemically Modified β-Cyclodextrins Can Encapsulate Small Hysupporting
confidence: 70%
“…4B). This efficacy was previously observed in other murine models (41,47,(56)(57)(58)(59), and provided the rationale for the clinical trials.…”
Section: Chemically Modified β-Cyclodextrins Can Encapsulate Small Hysupporting
confidence: 70%
“…[29][30][31][32][33] In the present study, we demonstrate that PLK1 inhibition with BI 2536 causes mitotic arrest in GBM cell lines, and that pretreatment with this drug efficiently sensitizes cells to radiation by decreasing proliferation and self-renewal in all the cell lines tested. Decreased proliferation after treatment with BI 2536 alone has already been demonstrated in different tumors: cervix adenocarcinoma, 24 leukemia, 34 anaplastic thyroid carcinoma, 35 melanomas, 15 and osteosarcoma cells. 25 Here, we also report that the combinatorial effect of BI 2536 with radiation was superior to treatment with the drug alone on cell proliferation, showing synergic effects.…”
Section: Pezuk Et Almentioning
confidence: 84%
“…Two independent RNAi studies both showed that the elimination of Plk1 function preferentially reduced the survival of cells with mutant p53 (25,26). There are also reports that anaplastic thyroid carcinoma (ATC), which has high frequency of p53 mutation (70-90%) and carries chromosomal instability signature, is profoundly sensitive to Plk1 inhibition by both siRNA knockdown study (44) and compound study (45). Interestingly, Aurora kinase inhibitor VX-680 was also shown to preferentially kill cancer cells with compromised p53 function, and a similar mechanism of weakened pseudo-G 1 tetraploidy checkpoint in p53-defective cells was proposed (46).…”
Section: Discussionmentioning
confidence: 99%